(untitled) (Archive of Conferences, 2021)
Teaching beautiful writing to primary school students is the foundation of literacy. Develop oral and written speech of Primary School students, educate them as mature people in every way,further improvement of the methods and ways to develop their beautiful writing skills by teaching a complex process, such as writing to students of small age, adult education as a schoolboy who aspires to beauty, who can feel it from the heart, who seeks to create beauty,the main goal of all primary school teachers is the formation of beautiful, on-demand, uniform writing skills of the husnixat of Primary School students of all secondary schools in the Republic.